Kajian Etnobotani Tumbuhan Jerangau (Acorus Calamus L) di Suku Dayak Sampit - Noorannisa, Luthfia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of the digital era in Indonesia cannot be denied. Along with the rapid progress of the digital era, the fulfillment of basic needs such as food, clothing and shelter is also increasing and limited. Efforts that can be made can be from recording, utilizing, planting in an agricultural business to preserving it which involves various fields of science, including Classification, Study of Ethnobotany Utilization and Biotechnology. Ethnobotany is a botanical science that studies the relationship between humans and plants. There are 6 studies in ethnobotany including botany, linguistics, ecology, pharmacology, economics, and anthropology. The Sampit Dayak community has various types of local plants that are used for daily life, both as food, herbal medicine, and even for traditional rituals, one of the plants that is still used today is jerangau (Acorus calamus L). This study used an interview method with the snowball sampling technique while plant samples were obtained from the environment around Baamang in Sampit, to then observe the morphology and ecology of the place where jerangau grows. In the botanical study, it was found that jerangau is a herbaceous plant that has fibrous roots, compound flowers, and single leaves. Linguistic studies state that jerangau comes from the word